Brugmansia suaveolens Bercht. & J. Presl: phytochemistry, cytotoxicity and its larvicidal activity against Aedes aegypti L. (Diptera: Culicidae) (Research, Society and Development, 2022)
The mosquito family (Diptera: Culicidae) contains several species of great public health relevance due to their role as vectors of human diseases. Aedes aegypti, is responsible for transmitting some of the most important vector-borne viruses that affect humanity, including Dengue, Chikungunya and Zika. The widespread and intensive use of chemical insecticides has caused significant adverse environmental effects and contributed to the emergence of populations, reducing their efficiency. Therefore, it becomes urgent to develop new alternative tools for vector control. In this context, our study aimed to trace the profile of the main secondary metabolites, followed by determining the larvicidal action against the A. aegypti mosquito lineage; and in vitro safety, through cytotoxicity in eukaryotic cells. The extracts were obtained by maceration with better yields for leaves, in relation to the phytochemical profile, the presence of different classes of secondary metabolites was identified, such as triterpenes, flavonoids, tannins, saponins and alkaloids. Low larvicidal lethality was observed at the concentrations tested (250-1000 ppm). The analysis of the cytotoxic potential showed a low toxic activity after direct exposure of the extracts to Saccharomyces cerevisiae cells, even though the species was classified as toxic. The study presented results not determined in previous research of this species, providing an innovative, relevant and significant character for future research.